Methodological and integration aspects of abc-method application in trade organizations - Guzaliya S., Klychova; Ilya V., Bagaev (Applied Studies in Agribusiness and Commerce, 2010)
In conditions of declining consumer demand and deficit of credit resources more and more managers of Russian companies think of necessity of introducing effective methods and systems of cost management. One of the most relevant is method of “Activity Based Costing” (ABC-method). Since, in western experts’opinion sectors of service and trade are adjusted to use ofABC-method even more than production, we should refer once more to the main methodological and integration aspects ofABC-method application and consider it from position of trade organization.